The planned TEN-T railway corridor "Baltic Sea - Black Sea - Aegean Sea" as an opportunity for economic development of Eastern Poland - Adam Dąbrowski; Robert Kruk; Krzysztof Ochociński (Przegląd Komunikacyjny, 2022)
Abstract: The article describes the basic requirements for the railway infrastructure of the comprehensive, extended core and core TEN-T network resulting from the draft of a new regulation of the European Parliament and of the Council (EU) on this matter. Then, the proposed TEN-T corridor “Baltic Sea – Black Sea – Aegean” is presented, which route is to lead largely through eastern and south-eastern Poland. This corridor, along with its considered link with the “Rail Baltica” route, fits well with the concept of the so-called eastern main line. The condition for creation of the corridor and the link is to ensure technical and operational parameters in accordance with the TEN-T requirements on the sections of railway lines included in their route, therefore the article assesses, what scope of investment works is related to the achievement of this goal and what adjustments and optimization measures should be considered. The creation of the corridor with the link may increase the transport accessibility of Polish regions located within their range of influence, and thus contribute to the economic development of these regions. Key words: accessibility, railway infrastructure